Description of three new water mite species of Hygrobates Koch, 1837 (Lurchibates Goldschmidt & Fu, 2011) (Acari, Hydrachnidia, Hygrobatidae), parasitic in newts of the genera Paramesotriton and Pachytriton (Amphibia, Caudata, Salamandridae) from China - Goldschmidt, Tom; Nishikawa, Kanto; Hiruta, Shimpei F.; Shimano, Satoshi (Zootaxa, 2020)
Males and females of three new water mite species of the genus Hygrobates Koch, 1837, subgenus Lurchibates Goldschmidt & Fu, 2011 (Acari, Hydrachnidia, Hygrobatidae) are described. The diagnosis of the subgenus is extended based upon the new material. The new species were all just found on one newt species each: Hygrobates (Lurchibates) intermedius sp. nov. Goldschmidt, Nishikawa & Shimano was collected from newts of the species Paramesotriton qixilingensis Yuan, Zhao, Jiang, Hou, He, Murphy & Che, 2014 from Jiangxi Province, China; H. (L.) robustipalpis sp. nov. Goldschmidt, Nishikawa & Shimano on Pachytriton inexpectatus Nishikawa, Jiang, Matsui & Mo, 2011 from Guizhou Province, China and H. (L.) pilosus sp. nov. Goldschmidt, Nishikawa & Shimano on Paramesotriton yunwuensis Wu, Jiang & Hanken, 2010 found in a pet shop.